2021
DOI: 10.1177/20416695211038265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Face Masks on the Emotional Reading Abilities of Children—A Lesson From a Joint School–University Project

Abstract: Wearing face masks has become a usual practice in acute infection events inducing the problem of misinterpreting the emotions of others. Empirical evidence about face masks mainly relies on adult data, neglecting, for example, school kids who firmly are dependent on effective nonverbal communication. Here we offer insights from a joint school–university project. Data indicate that emotional reading of 9 to 10 years old pupils ( N = 57) was similarly impaired as adults on an overall performance level, but that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 44 publications
11
68
2
7
Order By: Relevance
“…This study sheds light on the effects of wearing a mask, that is, the effects of occlusion of the mouth area on the recognition of different emotions in everyday contexts. These findings were also replicated with children age 9–10 years [ 15 ].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…This study sheds light on the effects of wearing a mask, that is, the effects of occlusion of the mouth area on the recognition of different emotions in everyday contexts. These findings were also replicated with children age 9–10 years [ 15 ].…”
Section: Introductionmentioning
confidence: 64%
“…Another group that requires special attention is children. In recent studies, researchers have found that children’s emotion recognition is also affected by facial masks [ 15 , 16 , 47 ]. Given that childhood is an important developmental stage for the socialization of emotion [ 48 , 49 ] and a potential influence of mask wearing on the development of necessary social interaction skills [ 18 ], it would be important not only to understand the effect of facial occlusion among children but also to develop strategies to help young children learn to read emotions from others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data indicate that the attentional response to a nonverbal spatial cue conveyed by gaze direction can be observed irrespective of face mask, and hence suggest that this micro-level component of social interaction is preserved. Interestingly, a recent study (Carbon & Serrano, 2021; see also Ruba & Pollak, 2020) has reported that children are not strongly affected by face masks in emotional reading. This, in turn, provides further evidence for the notion that face masks do not necessarily impair face processing mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Given the considerable importance of intact face processing in social interaction, it is important to understand how face masks affect face recognition. A great deal of studies have been dedicated recently to understanding the impact of face masks on various aspects of social interaction and cognition (Carbon, 2020 ; Carragher and Hancock, 2020 ; Freud et al, 2020 ; Green et al, 2020 ; Spitzer, 2020 ; Carbon and Serrano, 2021 ; Gori et al, 2021 ; Grundmann et al, 2021 ; Kastendieck et al, 2021 ; Marler and Ditton, 2021 ; Molnar-Szakacs et al, 2021 ; Noyes et al, 2021 ; Stajduhar et al, 2021 ). Many of these studies have demonstrated the detrimental effects of masks on the recognition of facial emotion and identity.…”
Section: Introductionmentioning
confidence: 99%